The neuroscience of risky decision making - Reyna, Valerie F., 1955-; Zayas, Vivian (Bronfenbrenner series on the ecology of human development., 2014)
"The topic of risky decision making is important for both personal decisions and for measurement and control in complex social institutions. (Think of pricing the mysterious "systemic risk" hidden in our highly interlocked financial systems, or avoiding pandemics.) Risky decision making is studied by researchers in a wide variety of disciplines. This book represents a current snapshot of what is known and a rough guide for future research on how to make sense of the complexity of risk. The editors' recipe: Create as much coherence across evidence from different disciplines as possible, and measure as much about underlying neural mechanisms as you can; then get top researchers working on their respective frontiers to say what they know in general language that makes shared understanding easy. A striking feature of this volume is how risk taking can be construed as fundamentally different, according to discipline. For traditional economists, risk is simply variance of outcomes, with no regard to their sign. Psychologists have shown the additional importance of loss, compared with gain--losses are often valued about 1.5 to 2 times as much as equivalent gains (unless you have amygdala damage, in which case traditional economics applies to you; DeMartino et al., 2010)"--Foreword. (PsycINFO Database Record (c) 2014 APA, all rights reserved).